Penerapan Self-Management dan PHBS untuk Mencegah Angka Kejadian Diare pada Remaja - Wulan Permatasari; Vina Aprelia; Tiya Rizki Novianti; Angga Antofani; Yuda Nugraha; Rini Fitriani; Triman Tresnawan; Dhani Andriansyah (Yayasan Inspirasi El Burhani, 2023)
Introduction: Diarrhea is a condition experienced by a person when the bowel movements are of an abnormal consistency, namely soft or liquid, the frequency of which can occur more than 3 times a day. Even if you have experienced severe diarrhea, the frequency can reach 10 times a day. Severe diarrhea can cause fluid loss and can be life-threatening, especially in children and adolescents who have nutritional deficiencies. Apart from causing fluid loss, there are also complications such as severe dehydration and even death. Objective: This community service aims to determine the effectiveness of self-management in PHBS as a form of effort to improve health and prevent diseases, especially diarrhea in adolescents at SMK Terpadu Al Hasan. Method: The methodology of health education that incorporates self-management. Participants in this counseling are anticipated to be able to apply a complete strategy, particularly in the creation of new behaviors, specifically PHBS in the school setting as well as the community. Result: Based on the results of pre- and post-implementation of Community service regarding the level of knowledge of the participants had increased. this shows that counseling with the application of self-management in PHBS has a positive impact on SMK Terpadu Al Hasan students. there is a significant effect before and after being given counseling. Conclusion: The conclusion from the implementation of health education activities regarding the application of self-management in PHBS in preventing diarrhea in adolescents is going according to plan. This activity is effective and has positive value for the students of SMK Terpadu Al Hasan. This can be seen from the enthusiasm and activeness of the participants in counseling as well as increased knowledge about self-management in PHBS in preventing diarrhea before and after being given counseling.